The level of speed and agility of different types of elite female basketball players - Erculj, F. M.; Bracic, M.; Jakovljevic, S. (Facta Universitatis: Series Physical Education and Sport, 2011)
In basketball, as in other team ball sports, speed is a complex ability which significantly affects playing performance. The aim of this study was to establish and analyze the development level of speed and agility of different types of female basketball players from the senior women`s national teams of Slovenia and Serbia. The guards, the forwards and the centers were compared, and any differences between them established. The study results showed a difference between individual player types in terms of body height and body weight, and some differences were also established in the tests of acceleration with the ball and without it. After eliminating the influence of body height and body weight, the differences in the speed of acceleration decrease and become statistically insignificant. The strongest influence was still observed in the S20 (the 20-metre sprint) and V20 (20-metre dribbling) tests, i.e. with the two variables in which ANOVA shows statistically significant differences between individual player types. In view of the study results, it can be concluded that body height and body weight significantly influence the speed of acceleration, i.e. cyclic speed, even among highly qualified female basketball players at a high international level, whereas the influence of the abovementioned morphological characteristics on the speed of performance of acyclic and agility movement is weaker.